Pengaruh Tingkat Pendidikan, Lama Usaha Dan Luas Lahan Terhadap Pendapatan Petani Tambak Udang Windu Di Desa Medokan Ayu Kecamatan Rungkut Kota Surabaya (International Forum of Researchers and Lecturers, 2023)
Surabaya city is one of the coastal cities in Indonesia and has potential in the fisheries sector. Apart from having a strategic role and having a large area of ​​land, the City of Surabaya can also increase its role as a shrimp pond farmer to increase natural resources for shrimp pond farmers in Surabaya. With good and optimal management can increase production and income levels so as to improve the welfare of the surrounding community. Especially for tiger shrimp pond farmers, it is hoped that they can provide employment and be able to become food ingredients providers. This study aims to prove and analyze the effect of education level, length of business and land area on the income of tiger shrimp pond farmers in Medokan Ayu Village, Rungkut District, Surabaya City. In this study using a causal quantitative approach. This study uses 1 dependent variable (income) and 3 independent variables (education level, length of business and land area). The type of research data used in this research is quantitative data. The data analysis method used in this study is multiple linear regression, F test (simultaneous), T test (partial), and the coefficient of determination. The results of this study indicate that the level of education (X1), length of business (X2) and land area (X3) simultaneously or together have a significant effect on the income of tiger shrimp pond farmers in Medokan Ayu Village, Rungkut District, Surabaya City. The level of education (X1) partially has a significant effect on the income of tiger shrimp pond farmers in Medokan Ayu Village, Rungkut District, Surabaya City. The length of business (X2) partially has no significant effect on the income of tiger shrimp pond farmers in Medokan Ayu Village, Rungkut District, Surabaya City. Land area (X3) partially has a significant effect on the income of tiger shrimp pond farmers in Medokan Ayu Village, Rungkut District, Surabaya City.